Mental Health Challenges during the COVID-19 Pandemic (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The aim of the reprint was to provide readers with updated research findings on the psychological and psychiatric consequences of the pandemic. The wide scope of the reprint reflects the complexity of the impact of the COVID-19 pandemic on mental health. The focus of the studies ranges from the psychological consequences of social distancing and the closure of schools to the neurological consequences of the viral infection, and from the stressful impact of an increased workload on frontline health workers to the unmet needs of special populations such as pregnant women, veterans and patients with neurodevelopmental disorders. Thanks to its richness in content and worldwide perspectives (contributors were from Canada, Croatia, Greece, India, Israel, Italy, Pakistan, the Philippines, Poland, Spain, and the USA), the reprint is a valuable source of information to researchers and clinicians interested in the mental health implications of the COVID-19 pandemic.